El Niño forecasting based on the global atmospheric oscillation. (3rd February 2020) - Serykh, Ilya V.; Sonechkin, Dmitry M.
Abstract: The predictability of El Niño and La Niña is investigated. In this case, the recently discovered so‐called global atmospheric oscillation (GAO) is considered. Assuming GAO to be the main mode of short‐term climatic variability, this study defines an index that characterizes the dynamics and relationships of the extratropical components of the GAO and El Niño – Southern Oscillation (ENSO). Due to the general propagation of the GAO's spatial structure from west to east, another index – predictor of ENSO is defined. The cross‐wavelet analysis between both of these indices and the Oceanic Niño Index (ONI) is performed. This analysis reveals a range of timescales within which the closest relationship between the GAO and ONI takes place. Using this relationship, it is possible to predict El Niño and La Niña with a lead‐time of approximately 12 months. Abstract : Due to the general propagation of the recently discovered global atmospheric oscillation's (GAO) spatial structure from west to east, El Niño's index‐predictor is defined. The cross‐wavelet analysis between index‐predictor and a standard El Niño index reveals a range of timescales within which the closest relationship between the GAO and El Niño takes place. Using this relationship, it is possible to predict El Niño with a lead time of approximately 12 months.